2010
DOI: 10.1155/2010/253465
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life, Mental Health and Psychotherapeutic Considerations for Women Diagnosed with a Disorder of Sexual Development: Congenital Adrenal Hyperplasia

Abstract: Little is known about the long-term health-related quality of life (HRQL) and mental health outcomes for women diagnosed with congenital adrenal hyperplasia (CAH), a disorder of sex development. Though recommendations for therapists exist, no research has empirically investigated women's experiences in therapy or their recommendations for therapy. Thus the purpose of the study was to investigate HRQL, mental health concerns of women with CAH, and patients' recommendations for therapists. A qualitative methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 23 publications
0
42
0
Order By: Relevance
“…Previous research on HRQOL in CAH patients has primarily focused on adults [2,3,4,5,6,7,14], whereas pediatric data have been limited. A recent study from the Netherlands documented few negative effects of the disease on physical, social, and societal functioning [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on HRQOL in CAH patients has primarily focused on adults [2,3,4,5,6,7,14], whereas pediatric data have been limited. A recent study from the Netherlands documented few negative effects of the disease on physical, social, and societal functioning [8].…”
Section: Discussionmentioning
confidence: 99%
“…Among women with CAH, concerns regarding fertility, increased anxiety about disclosing the diagnosis to others, and decreased satisfaction with sexual functioning have been reported [3,4]. However, other data also suggest that patients function normally and have a good overall psychological adjustment [5]. Most recently, a study of 588 CAH adults in Sweden showed that the total cohort of CAH patients did not differ greatly from the general population in terms of education, employment, income, sick leave, disability pension, social welfare, marriage, or children [6].…”
Section: Introductionmentioning
confidence: 99%
“…Female participants view looking feminine in a positive sense, whereas masculine appearance is a negative concern and a source of lower self-esteem (Alderson et al, 2004;MacKenzie et al, 2009;Malouf et al, 2010):…”
Section: Lower Self-esteemmentioning
confidence: 99%
“…Other coping strategies employed by participants include positives thinking, searching for family history, sense of difference, openness, willingness to share personal information, and acceptance (Alderson et al, 2004;Guth et al, 2006;Malouf et al, 2010). .…”
Section: Coping Strategiesmentioning
confidence: 99%
“…Varying degrees of impaired QoL have been described [59,60,74,79,[93][94][95][96]. In a few publications, no difference from controls was found [97][98][99] and, in one study, even a better QoL compared to controls was reported [100]. Moreover, CAH patients were reported to have a better QoL compared to patients with primary adrenal insufficiency [94].…”
Section: Quality Of Lifementioning
confidence: 99%